Recombinant MS087-based indirect ELISA for the diagnosis of Mycoplasma synoviae - Zhang, Yang; Wu, Yan; He, Jiawei; Lai, Jiacui; Ding, Honglei (Frontiers in Veterinary Science, 2024)
Accurate detection is a prerequisite for effective prevention and control of Mycoplasma synoviae infection. ELISA is the most popular method for the clinical detection of M. synoviae because of its convenience, low cost, and high detection rate. However, the cross-reactivity of commercially available ELISA kits with other avian pathogen-positive sera needs to be addressed. The aim of this study was to establish an ELISA method with high specificity for the detection of anti-M. synoviae antibodies in chicken serum to evaluate the M. synoviae infection status on poultry farms. The recombinant MS087 (rMS087) protein was expressed in Escherichia coli BL21 (DE3) and purified by Ni2+ affinity chromatography. An antibody against rMS087 was generated by immunizing BALB/c mice. Bioinformatic analysis revealed that MS087 was conserved among M. synoviae strains. Western blotting and indirect immunofluorescence results indicated that MS087 was not only localized in the cytoplasm and on the membrane but also secreted by the organism. For the established ELISA method based on rMS087, the optimal antigen concentration, blocking buffer, blocking duration, serum dilution, serum incubation duration, secondary antibody dilution, secondary antibody incubation duration and colorimetric reaction duration were 2 μg/mL, 1% BSA, 3 h, 1:500, 1.5 h, 1:20,000, 2 h and 5 min, respectively. Validation of the rMS087-based ELISA revealed a cut-off value of 0.5. The coefficients of variation of both the intra-batch and inter-batch methods were less than 9%. The assay was able to differentiate positive serum against M. synoviae from antisera against nine other avian pathogens and was able to recognize M. synoviae-positive sera at a dilution of 1:1,000. Compared with the commercial ELISA method, the rMS087-based ELISA has the potential to recognize more positive sera against M. synoviae. Collectively, the rMS087-based ELISA is a reproducible, specific, and sensitive serological method for detecting antibodies against M. synoviae in chicken serum and has robust potential for large-scale serological epidemiology of M. synoviae infection on poultry farms.